Leadership for a Changing Church : Charting the shape of the river - Dale, Robert D. (Abingdon Press, 1998)
Drawing on a metaphor from Mark Twain's Life on the Mississippi, Robert Dale claims that religious leaders must know, as never before, the "shape of the river" of religious and social change. Change, he argues, is the primary context in which Christian ministry now takes place. Pastors and other congregational leaders must embody the timeless values of the Christian message, yet do so in ways that are constantly flexible and open to revision. Fundamental to religious leaders in this new era will be adaptability rooted in character. Leadership for a Changing Church will enable readers to look ahead in anticipation, as they welcome the new challenges presented by ministry in an ever-evolving era